Evaluating the use of eggshell powder and sawdust ash as cement replacements in sustainable concrete development - Ajoy Kumer; Md. Arif Arman Akash; Pritom Dey; Faysal Montasir; Kaysarul Islam Bhuiyan; Farhan Fahad (Journal of Sustainable Construction Materials and Technologies)
Concrete, the most widely utilized material in construction worldwide, contributes significantly tothe consumption of natural resources and energy. The construction sector is a major source of wasteand greenhouse gas (GHG) emissions, making it essential to improve the environmental impact ofconcrete to address climate change and pollution concerns. Evaluating the environmental footprint ofconcrete is crucial for advancing sustainable building practices. Cement, a key binder in concrete, isparticularly responsible for GHG emissions due to its energy-intensive production process. This studyapplies the Life Cycle Assessment (LCA) methodology, using SimaPro software and the Ecoinventdatabase, to assess the environmental impact of concrete. A modified concrete mix was developed byreplacing Portland Composite Cement with Eggshell Powder (ESP) (60% by weight) and Sawdust Ash(SDA) (40% by weight) at varying replacement rates of 10%, 20%, 30%, and 40%. The results showedup to 20% for replacement cement with ESP and SDA improved compressive strength in a 28-56 dayperiod, with the highest strength growth rate of 29.58% observed for the mixes with replacement.However, higher replacement levels of 30% and 40% showed limited strength improvement duringthe same period. The enhanced compressive Strength and higher strength growth (compared to tra-ditional concrete) are observed withare0-20 % replacement of cement s. This suggests that this blendof materials could be used in projects with significant budget constraints, directly decreasing carbonemissions associated with concrete production. This aligns with global sustainability goals and can beused in projects aiming for green certifications like LEED (Leadership in Energy and EnvironmentalDesign). The study indicates that substituting cement with ESP and SDA reduces costs. This can sig-nificantly benefit low-budget housing projects or areas with high cement prices, providing a directeconomic advantage. The environmental performance of the modified concrete was analyzed throughLCA following the ISO 14040:2006 framework, focusing on the cradle-to-grave impacts, including rawmaterial extraction, energy consumption, and water usage. One cubic meter of concrete was chosenas the functional unit. The analysis revealed significant reductions in the endpoint impact categories,including a 59% reduction in ecosystem impacts, 60% in human health, 61% in resource depletion,59.79% in ozone depletion, and 54.32% in fossil fuel depletion. These results highlight the potential ofESP and SDA as sustainable alternatives for improving concrete's mechanical properties and environ-mental performance, supporting the development of more sustainable construction practices.